The role of acid-base imbalance in statin-induced myotoxicity - Taha, Dhiaa A.; de Moor, Cornelia H.; Barrett, David A.; Lee, Jong Bong; Gandhi, Raj D.; Hoo, Chei Wei; Gershkovich, Pavel (Elsevier, 2016)
Disturbances in acid-base balance, such as acidosis and alkalosis, have potential to alter the pharmacological and toxicological outcomes of statin therapy. Statins are commonly prescribed for elderly patients who have multiple co-morbidities such as diabetes mellitus, cardiovascular and renal diseases. These patients are at risk of developing acid-base imbalance. In the present study, the effect of disturbances in acid-base balance on the inter-conversion of simvastatin and pravastatin between lactone and hydroxy acid forms have been investigated in physiological buffers, human plasma and cell culture medium over pH ranging from 6.8 to 7.8. The effects of such inter-conversion on cellular uptake and myotoxicity of statins were assessed in vitro using C2C12 skeletal muscle cells under conditions relevant to acidosis, alkalosis and physiological pH. Results indicate that the conversion of the lactone forms of simvastatin and pravastatin to the corresponding hydroxy acid is strongly pH-dependent. At physiological and alkaline pH, substantial proportions of simvastatin lactone (~ 87% and 99%, respectively) and pravastatin lactone (~ 98% and 99%, respectively) were converted to the active hydroxy acid forms after 24 hours of incubation at 37 °C. At acidic pH, conversion occurs to a lower extent, resulting in greater proportion of statin remaining in the more lipophilic lactone form. However, pH alteration did not influence the conversion of the hydroxy acid forms of simvastatin and pravastatin to the corresponding lactones. Furthermore, acidosis has been shown to hinder the metabolism of the lactone form of statins by inhibiting hepatic microsomal enzyme activities. Lipophilic simvastatin lactone was found to be more cytotoxic to undifferentiated and differentiated skeletal muscle cells compared to more hydrophilic simvastatin hydroxy acid, pravastatin lactone and pravastatin hydroxy acid. Enhanced cytotoxicity of statins was observed under acidic conditions and is attributed to increased cellular uptake of the more lipophilic lactone or unionized hydroxy acid form. Consequently, our results suggest that co-morbidities associated with acid-base imbalance can play a substantial role in the development and potentiation of statin-induced myotoxicity.